HUBUNGAN KUALITAS TIDUR, LAMA KERJA, DAN KELELAHAN MATA TERHADAP KEJADIAN MINOR INJURY DI INDUSTRI RUMAHAN SEPATU KULIT LACOSTA DESTA SHOESKUALITAS TIDUR, LAMA KERJA, DAN KELELAHAN MATA TERHADAP KEJADIAN MINOR INJURY DI INDUSTRI RUMAHAN SEPATU KULIT LACOSTA DESTA SHOES - Dalliantika Muthia Zahra; Ari Suwondo; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2020)
Individual characteristics, job, and work environment must be mutually supportive to achieve a good implementation of safety and health in the workplace. Lacosta Desta Shoes produces leather shoes through a process that includes tools and materials that are at risk of causing minor injury. Minor injury is a type of work accident that can injure workers but does not require medical treatment and does not eliminate work hours. A fatal work accident can occur if a minor injury is not handled properly. This study aims to analyze the correlation between sleep quality, work hours, visual fatigue, and the occurrence of minor injury. This study uses observational analytic methods and cross-sectional studies. Sampling was performed by using a total sampling method which covers the entire population of Lacosta Desta Shoes workers as many as 15 people. The research instruments are a questionnaire sheet for individual characteristics and work hours, a checklist for visual fatigue and the occurrence of minor injury, and a standard PSQI questionnaire for sleep quality. Data analysis uses a chi-square statistical test. The results showed there was a correlation between visual fatigue with work tenure (????=0.033), nutritional status (????=0.011), sleep quality (????=0.033), and work hours (????=0.001) and there was a correlation between the occurrence of a minor injury with work hours (????=0.009) and visual fatigue (????=0.009). There was no correlation between visual fatigue with age (????=1.000), refractive abnormalities (????=0.231), and metabolic disease (????=1.000) with visual fatigue and no correlation between the occurrence of a minor injury with sleep quality (????=0.154). There are 12 workers (80%) who have experienced minor injuries in the last 3 months. Lacosta Desta Shoes can prevent and reduce the occurrence of minor injury toward workers through periodic visual health check-ups, work hours adjustment, and the provision of first aid kits in the shoe repair shops.